2018
DOI: 10.13040/ijpsr.0975-8232.9(12).5320-26
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Ultraviolet radiation (UV) from sun has significant detoriating and degenerative effects on human skin and thus responsible for much skin disease. The most authentic and realistic approach to overcome this issue is to use or apply a barrier between sun rays and exposed skin surface using suitable products called sunscreens or UV protectors. Sunscreens usually include both natural and synthetic molecule and have great application in cosmaceuticals. In the present study one such natural product-rose water was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…hydrosol [ 30 ], with no available research on its anticytotoxic and antigenotoxic effects. The data obtained in our previous study on the antioxidant properties of rose hydrosol [ 22 ] and the results reported in [ 31 ] with respect to the photoprotective and antioxidant activity of R. damascena Mill. hydrosol provoked us to test the anticytotoxic and antigenotoxic effects of rose hydrosol.…”
Section: Introductionmentioning
confidence: 66%
“…hydrosol [ 30 ], with no available research on its anticytotoxic and antigenotoxic effects. The data obtained in our previous study on the antioxidant properties of rose hydrosol [ 22 ] and the results reported in [ 31 ] with respect to the photoprotective and antioxidant activity of R. damascena Mill. hydrosol provoked us to test the anticytotoxic and antigenotoxic effects of rose hydrosol.…”
Section: Introductionmentioning
confidence: 66%